2021
DOI: 10.1177/10570837211034136
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Critical Reflection and Productive Dialogue in Music Teacher Education

Abstract: Because teaching is an inherently political act, it is important for music teacher educators to consider their role in the public discourse and how they approach the political dimensions of teaching with future music educators. In this interest article, we offer a theoretical basis for engaging preservice music teachers in critical reflection and productive dialogue throughout their undergraduate music education coursework. In combination with theory, we describe specific strategies for designing environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this sense, Harry and Salvador [ 25 ] consider that teaching is a political act by nature. Therefore, they assert that teacher educators should consider their public discourses and how they approach the political dimensions of teaching with pre-service teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Harry and Salvador [ 25 ] consider that teaching is a political act by nature. Therefore, they assert that teacher educators should consider their public discourses and how they approach the political dimensions of teaching with pre-service teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, teacher educators held a prominent role through their own teaching practices, as they are expected to generate contexts promoting critical reflection and awareness. Harry and Salvador [ 25 ] affirm that teaching is an inherently political act. Therefore, they highlight that teacher educators should be conscious of their role in the public discourse and how they tackle the political dimensions of teaching with pre-service teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Both preservice and inservice music teachers are encouraged to reflect regularly on their lesson effectiveness. Researchers have found that the ability to reflect accurately and effectively is a skill that can be developed and requires practice (Abramo & Campbell, 2016; Bond, 2022; Burnard, 2006; Chaffin & Manfredo, 2010; Conway, 2020; Harry & Salvador, 2021; Rosaen et al, 2008; Springer & Yinger, 2019). To develop as music teachers, preservice teachers need opportunities to practice teaching (Duke, 2014) alongside opportunities for guided self-reflection (Blackwell & Roseth, 2018).…”
mentioning
confidence: 99%
“…Facilitating self-reflection for preservice teachers may be done in a variety of ways, such as journaling, group work, collective discourse, and learning logs (Conkling, 2003). Researchers have devised various systems to facilitate self-reflection (Austin, 2021; Blackwell & Roseth, 2018; Bond, 2022; Burnard, 2006; Harry & Salvador, 2021; Parker & Powell, 2014; Rosaen et al, 2008). For example, Blackwell and Roseth (2018) implemented a five-step system within a peer teaching setting, which ended in reflection and enabled preservice music teachers to feel “in charge of their learning” (p. 63).…”
mentioning
confidence: 99%